The effect of childhood education on old age cognitive abilities: Evidence from a regression discontinuity design - Fabrizio Mazzonna; James Banks (Institute for Fiscal Studies (IFS), 2011)
We exploit the change to the minimum school-leaving age in the United Kingdom from 14 to 15 using a regression discontinuity design to evaluate the causal effect of one more year of education on cognitive abilities at older ages. We find a large and significant effect of this reform on males' memory and executive functioning measured using simple cognitive tests from the English Longitudinal Survey on Ageing (ELSA). This result is particularly remarkable since the 1947 reform had a powerful and immediate effect on about half the population of 14-yearolds. We investigate and discuss the potential channels by which this reform may have had its effects, as well as carrying out a full set of sensitivity analyses and robustness checks.
Keywords: C14; I28; J14; J24; 330; Cognitive abilities; education; aging; regression discontinuity design; ELSA